Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Our Q&A platform offers a seamless experience for finding reliable answers from experts in various disciplines. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

[tex]22y = 11(3 + y)[/tex]I need help with my homework cause I'm sorta slow

Sagot :

Given the expression:

[tex]22y=11(3+y)[/tex]

First we need to get rid of the parenthesis by multiplying 11 by 3 and by y:

[tex]\begin{gathered} 22y=11(3+y) \\ \Rightarrow22y=33+11y \end{gathered}[/tex]

Now we solve for y:

[tex]\begin{gathered} 22y=33+11y \\ \Rightarrow22y-11y=33 \\ \Rightarrow11y=33y \\ \Rightarrow y=\frac{33}{11}=3 \\ y=3 \end{gathered}[/tex]

Therefore, y=3